The effects of intensity and duration of aerobic exercise on spatial memory function in male Wistar rats (Medical Journal of Indonesia, 2019)
BACKGROUND Memory is a vital function of the brain. Aerobic exercise has a positive effect on memory's function, but the appropriate combination of intensity and duration of aerobic exercise is still unknown. This study was aimed to investigate the effect of optimum combinations of intensity and duration of aerobic exercise on spatial memory function. METHODS In this study, the authors performed in vivo experiment using 20 male Wistar rats (6-month-old). They were randomly divided into four groups: (1) low-intensity and short duration aerobic exercise group (L-S); (2) low-intensity and long duration aerobic exercise group (L-L); (3) high-intensity and short duration aerobic exercise group (H-S); and (4) high-intensity and long duration aerobic exercise group (H-L). The aerobic exercise treatment of each group was conducted for three weeks with a frequency of five days a week. The memory function was assessed with the help of water-E-maze on week 0, 1, 2, and 3 (a total of four times). RESULTS This study indicates that the central nervous system responds to aerobic exercise as an external stimulus differently depending on the combinations of intensity and duration. Moreover, this study demonstrates that changes in memory functions are best observed in the group with low-intensity and long duration aerobic exercise. CONCLUSIONS The combination of low-intensity and long duration of aerobic exercise for animal study can improve spatial memory functions better than any other combinations of intensity and duration of aerobic exercises in male Wistar rats.